Penerapan Lean Manajemen pada Pelayanan Rawat Jalan Pasien BPJS Rumah Sakit Hermina Depok Tahun 2017 - Noviani, Elisabeth Dyah (Jurnal ARSI : Administrasi Rumah Sakit Indonesia, 2017)
The length of waiting time in the hospital outpatient service is important for efficient hospital service. Long waiting time leads to accumulating queue and inefficient service. This study was aimed to analyze the application of lean method on outpatient BPJS services at Hermina Depok Hospital in 2017. This qualitative research method investigated the time spent by BPJS outpatient patient by applying lean method and observing the outpatient service flow condition. The results showed that 90% service time was a non-value added activities and only 10% of value-added activities. After conducting future state analysis with the proposed improvement with simulative lean method (5S, Kanban Inventory, visual management), it was found that non value added activity became 78,30% and value added activity became 21,70%.